Optimal fermentation of Shuanghuanglian and its effects on production performance of laying hens - Xu, Yongqing; Yi, Siyu; Xu, Xiaojie; Zhang, Minghui; Cui, Yadong; Lan, Wei; Li, Fenglan; Kong, Xiangfeng (Frontiers in Veterinary Science, 2024)
BackgroundShuanghuanglian is a Chinese medicine composed of Honeysuckle Flower, Baical Skullcap Root, and Fructus Forsythiae. It has various effects, including anti-inflammatory, antibacterial, antiviral, and immunomodulatory effects. The fermented product of Shuanghuanglian can be used as an antibiotic alternative, as it has similar efficacy, which may improve the immunity, feed intake and utilization efficiency of laying hens, thus improving their production performance. The aim of this study was to optimize the fermentation conditions for Shuanghuanglian using single factor and response surface methodology, evaluate the chemical and microbial composition of the Shuanghuanglian fermentation liquor (SFL), and explore the effects of SFL on the production performance of laying hens.MethodsA total of 288 Xinyang black-feather laying hens (50 week-old) were randomly allocated to four treatments with nine replicates, each replicate containing eight hens, for a total of 37 days trial (including a 7-day adaptation period). The treatments included a control group (0% SFL in drinking water) and drinking water supplemented with 0.3, 0.5, or 0.7% SFL.ResultsThe fermentation optimization conditions for Shuanghuanglian were selected as a solid-to-liquid ratio at 1:7, 3% inoculation quantity, fermentation temperature at 28°C for 5 days, initial pH of 7, 60 mesh (sieved), and rotation speed of 150 r/min. Various bioactive compounds, such as myrtenol, 2-hexyn-1-ol, arsenous acid tris(trimethylsilyl) ester, 3(10)-caren-4-ol, and oxime-, methoxy-phenyl, were detected in SFL. The most abundant bacterial phyla in SFL were Proteobacteria and Firmicutes, with Acinetobacter being the most abundant genus. The most abundant fungal phyla were Phragmoplastophyta and Magnoliophyta. The 0.5 and 0.7% SFL supplementation in water increased egg weight and laying rate, while decreasing the feed-to-egg ratio of laying hens compared with the control group (p < 0.05). Additionally, 0.3, 0.5, and 0.7% SFL supplementation in water increased (p < 0.05) the Haugh unit, but there were no significant differences (p > 0.05) in albumen height, egg shape index, egg thickness, and yolk color of the eggs.ConclusionSupplementation of SFL under optimized conditions had a positive impact on the production performance of laying hens, especially when the supplementation amount reached 0.5%. This study provides a theoretical basis for the application of Shuanghuanglian in the commercial egg industry.